Post‐PCI quantitative flow ratio predicts 3‐year outcome after rotational atherectomy in patients with heavily calcified lesions. Issue 5 (21st March 2022) - You, Wei; Zhou, Yuhe; Wu, Zhiming; Meng, Peina; Pan, Defeng; Yin, Delu; Yang, Song; Wu, Xiangqi; Ye, Fei
Abstract: Background: The study sought to investigate the clinical predictive value of quantitative flow ratio (QFR) for the long‐term outcome in patients with heavily calcified lesions who underwent percutaneous coronary intervention (PCI) following rotational atherectomy (RA). Methods: In this retrospective study, 393 consecutive patients from 2009 to 2017 were enrolled. The QFR of the entire target vessel (QFRv) and the QFR of the stent plus 5 mm proximally and distally (in‐segment) (QFRi) were measured. The primary endpoint was target lesion failure (TLF), including target lesion‐cardiac death (TL‐CD), target lesion‐myocardial infarction (TL‐MI), and clinically driven‐target lesion revascularization (CD‐TLR). Results: A total of 224 patients with 224 calcified lesions completed the clinical follow‐up, and 52 patients had TLF. There was no significant difference in QFRv post‐PCI between non‐TLF and TLF groups ( p  > .05). However, QFRi post PCI was significantly higher in the non‐TLF group than in the TLF group. Multivariate Cox regression showed that QFRi post‐PCI was an excellent predictor of TLF after a 3‐year follow‐up (HR 1.7E −8 [5.3E −11 –5.6E ‐6 ]; p  < .01). Furthermore, receiver‐operating characteristic curve analysis demonstrated that the optimal cutoff value of QFRi for predicting the long‐term TLF was 0.94 (area under the curve: 0.826, 95% confidence interval: 0.756–0.895; sensitivity: 89.5%, specificity: 69.2%; p  < .01). The QFRi ≤ 0.94 post‐PCI was negatively associated with TLF, including TL‐CD, TL‐MI, and CD‐TLR ( p  < .01). Conclusions: QFRi post‐PCI showed a high predictive value for TLF for during a 3‐year follow‐up in patients who underwent PCI following RA; specifically, lower QFRi values post‐PCI were associated with worse TLF.